2022
DOI: 10.1007/s00167-022-07158-1
|View full text |Cite
|
Sign up to set email alerts
|

No advantage with navigated versus conventional mechanically aligned total knee arthroplasty—10 year results of a randomised controlled trial

Abstract: Purpose Computer-assisted surgery (CAS) total knee arthroplasty (TKA) remains a controversial area of surgical practice. The aim of this study is to report the ten-year revision rates and patient-reported outcome measures (PROMS) of a single-blinded, prospective, randomised controlled trial comparing electromagnetically (EM) navigated and conventional TKA. Methods 199 patients were randomised to receive either EM navigated or conventional TKA where the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In contrast, several authors stated that no relevant differences were found between the groups. Kim et al found no difference between groups [ 20 ] for the WOMAC scale and other functional scores and activities, whereas Farhan-Alanie et al [ 21 ] found no difference in the KSS and Oxford knee scores. At the same time, Ollivier et al [ 10 ] found no difference in the SF-12, FJS, KSS or knee injury and osteoarthritis outcome score (KOOS).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several authors stated that no relevant differences were found between the groups. Kim et al found no difference between groups [ 20 ] for the WOMAC scale and other functional scores and activities, whereas Farhan-Alanie et al [ 21 ] found no difference in the KSS and Oxford knee scores. At the same time, Ollivier et al [ 10 ] found no difference in the SF-12, FJS, KSS or knee injury and osteoarthritis outcome score (KOOS).…”
Section: Discussionmentioning
confidence: 99%